Identification of proteins associated with development of metastasis from cutaneous squamous cell carcinomas (cSCCs) via proteomic analysis of primary cSCCs. (24th September 2020) - Shapanis, A.; Lai, C.; Smith, S.; Coltart, G.; Sommerlad, M.; Schofield, J.; Parkinson, E.; Skipp, P.; Healy, E.
Summary: Background: Cutaneous squamous cell carcinoma (cSCC) is one of the most common cancers capable of metastasizing. Proteomic analysis of cSCCs can provide insight into the biological processes responsible for metastasis, as well as future therapeutic targets and prognostic biomarkers. Objectives: To identify proteins associated with development of metastasis in cSCC. Methods: A proteomic‐based approach was employed on 105 completely excised, primary cSCCs, comprising 52 that had metastasized (P‐M) and 53 that had not metastasized at 5 years post‐surgery (P‐NM). Formalin‐fixed, paraffin‐embedded cSCCs were microdissected and subjected to proteomic profiling after one‐dimensional (1D), and separately two‐dimensional (2D), liquid chromatography fractionation. Results: A discovery set of 24 P‐Ms and 24 P‐NMs showed 144 significantly differentially expressed proteins, including 33 proteins identified via both 1D and 2D separation, between P‐Ms and P‐NMs. Several differentially expressed proteins were also associated with survival in SCCs of other organs. The findings were verified by multiple reaction monitoring on six peptides from two proteins, annexin A5 (ANXA5) and dolichyl‐diphosphooligosaccharide–protein glycosyltransferase noncatalytic subunit (DDOST), in the discovery group and validated on a separate cohort ( n = 57). Increased expression of ANXA5 and DDOST was associated with reduced time to metastasis in cSCC and decreased survival in cervical and oropharyngeal cancer. A prediction model using ANXA5 and DDOST had an area under the curve of 0·93 (confidence interval 0·83–1·00), an accuracy of 91·2% and higher sensitivity and specificity than cSCC staging systems currently in clinical use. Conclusions: This study highlights that increased expression of two proteins, ANXA5 and DDOST, is significantly associated with poorer clinical outcomes in cSCC. Abstract : What is already known about this topic? Keratinocyte cancer is the most common cancer in the UK, and the capacity for cutaneous squamous cell carcinomas (cSCCs) to metastasize presents a clinical problem. Although there are known clinical risk factors for cSCC metastasis, current staging systems are inaccurate at predicting the development of metastasis in patients with cSCC. It has been shown that mass spectrometry‐based proteomic analysis can quantify and uncover potential key proteins in cancer development and metastasis. What does this study add? This study has identified a number of proteins that are differentially expressed between primary cSCCs that metastasize and primary cSCCs that do not metastasize. Expression of the genes encoding several of these proteins influences the outcome in SCCs of other organs (lung, oropharynx, cervix and oesophagus). Higher abundances of two key proteins, annexin A5 (ANXA5) and dolichyl‐diphosphooligosaccharide–protein glycosyltransferase noncatalytic subunit (DDOST), are associated with the development of, and reduced time to, cSCC metastasis. What is the translational message? This is the first study to undertake proteomic profiling using mass spectrometry to investigate proteins that are differentially expressed between human primary cSCCs that metastasize and those that do not metastasize. The results of this proteomic analysis of cSCCs will be useful for identifying potential therapeutic targets in this cancer. A prediction model incorporating ANXA5 and DDOST showed higher sensitivity and specificity than cSCC clinical staging systems for estimating the likelihood of cSCC metastases. Linked Comment: Tobin. Br J Dermatol 2021; 184 :593–594 .